The Correlation Between Students' Basic Literacy Skills and Digital Readiness Index in the Context of Preparing for Golden Indonesia 2045 - Setyawan, Agung; Citrawati, Tyasmiarni (Universitas Trunojoyo Madura, 2023)
This study aims to analyze the relationship between students' basic literacy skills (reading, writing, and arithmetic) and their digital readiness index, as well as its implications for building superior human resources toward Indonesia Emas (Golden Indonesia) 2045. This quantitative research employs an ex post facto approach, involving 350 elementary school students from five Indonesian provinces as samples. Data were collected through basic literacy tests (PISA-standardized) and a digital readiness questionnaire measuring four aspects: digital skills, technology access, information literacy, and attitudes toward technology. Statistical analysis was conducted using Pearson correlation and linear regression tests to identify relationship patterns. The results show a significant positive correlation between basic literacy skills and the digital readiness index (r = 0.62, p 0.01). Students with higher literacy levels tend to have better technology adaptation abilities, particularly in information literacy (β = 0.48). These findings support the hypothesis that basic literacy serves as a critical foundation for mastering digital competencies in the era of the 4.0 industrial revolution. However, regional disparities were observed in technology access, which moderates the strength of the relationship. This study highlights the urgency of enhancing technology-based basic literacy as a strategy to achieve the 2045 superior human resources target. Policy recommendations include integrating digital content into literacy curricula and equalizing technology infrastructure in underdeveloped regions.